2019
DOI: 10.1097/md.0000000000017438
|View full text |Cite
|
Sign up to set email alerts
|

Association between ADAMTS7 polymorphism and carotid artery plaque vulnerability

Abstract: Recent genome-wide association studies (GWAS) indicated that polymorphisms in ADAMTS7 were associated with artery disease caused by atherosclerosis. However, the correlation between the ADAMTS7 polymorphism and plaque stability remains unclear. The objective of this study was to evaluate the association between 2 ADAMTS7 variants rs3825807 and rs7173743 and ischemic stroke or atherosclerotic plaque vulnerability.This research is an observational study. Patients with ischemic stroke and normal control individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Thus, our results are in keeping with prior reports that this variant is likely to explain at least a portion of the CAD associated risk at this locus. [6][7][8][9][10] Before ADAMTS7 was reported as CAD genomewide association studies locus, it was demonstrated that ADAMTS7 knockdown prevented, while ADAMTS7 overexpression increased, neointima formation in a rat carotid artery vascular injury model. 12 Mouse knockout studies confirmed that total loss of function reduced neointima formation in the carotid 13 and femoral arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results are in keeping with prior reports that this variant is likely to explain at least a portion of the CAD associated risk at this locus. [6][7][8][9][10] Before ADAMTS7 was reported as CAD genomewide association studies locus, it was demonstrated that ADAMTS7 knockdown prevented, while ADAMTS7 overexpression increased, neointima formation in a rat carotid artery vascular injury model. 12 Mouse knockout studies confirmed that total loss of function reduced neointima formation in the carotid 13 and femoral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results are in keeping with prior reports that this variant is likely to explain at least a portion of the CAD associated risk at this locus. 6–10…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] A recent report stated that the ADAMTS7 variants rs3825807 and rs7173743 were related to the risk of carotid plaque vulnerability. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The Ser214 risk variant was shown to increase prodomain processing and maturation, correlating with an increase in COMP (Cartilage oligomeric matrix protein) degradation and vascular smooth muscle cell migration (4). Additionally, the Ser214 risk allele was associated with an unstable atherosclerotic plaque phenotype and an increase in secondary cardiac events (5)(6)(7)(8). Mouse knockout studies have shown that Adamts7 loss-offunction significantly reduces vascular smooth muscle cell mediated neointimal formation in arterial wire injury models (9,10).…”
Section: Introductionmentioning
confidence: 99%